PENGARUH PEMBERIAN VARIASI DOSIS JAMUR TRICHODERMA SP TERHADAP PENINGKATAN PERKECAMBAHAN KACANG TANAH (Arachis hypogaea L.) - Joko A Untung; Bertje. R. A. Sumayku; M. G. M Polii (Universitas Sam Ratulangi, 2019)
ABSTRACT The research objective is to study the effect of Trichoderma sp mushroom dosage variations on the increase in seed germination of peanut plants was carried out at the Green House, Faculty of Agriculture, Unsrat. for 3 months, starting in June - August 2019. This study uses a completely randomized design method (CRD), with 6 treatments in a ratio of 1: 0, 1: 1, 1: 2, 1: 3, 1: 4, and 1: 5 The results of the analysis of varying doses of Trichoderma sp on peanut seeds showed a difference to the germination of peanut seeds compared with seeds that did not use trichoderma sp. This can be influenced by several factors that inhibit germination, namely internal factors including hormones, seed size, maturity, and dormancy. Seeds that are harvested before physiological maturity do not have high viability because they do not have sufficient food reserves and imperfect embryo formation. Key words:Trichoderma, peanuts